2001
DOI: 10.1080/714052705
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome following fetal single umbilical artery diagnosis

Abstract: Pregnancies complicated by fetal single umbilical artery, especially when associated with other congenital abnormalities, are at increased risk for adverse pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…This finding is in agreement with Pierce et al . who demonstrated a higher rate of CS in the isolated SUA group in comparison to non‐isolated SUA pregnancies (41% vs 13%, p < 0.05) …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding is in agreement with Pierce et al . who demonstrated a higher rate of CS in the isolated SUA group in comparison to non‐isolated SUA pregnancies (41% vs 13%, p < 0.05) …”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, data on the association of isolated SUA with labor and delivery outcome are scarce. Although some suggested an increased rate of adverse outcome such as cesarean section (CS) in pregnancies complicated by isolated SUA, several of the findings reported are limited by small sample size and limited information on the reasons for the higher rate of adverse outcome.…”
Section: Introductionmentioning
confidence: 99%
“…However, while even recent reports in high‐risk populations support the evidence for an increased prevalence of CHD15–21, it has also been reported that in pregnancies with an apparently isolated SUA, fetal echocardiography is not necessary if normal four‐chamber and outflow tract views of the fetal heart have been obtained22. This change in approach is justified by the fact that national and international guidelines—for example, the guidelines of the International Society of Ultrasound in Obstetrics and Gynecology in the approach defined as the ‘extended basic’ cardiac scan23—are increasingly supporting the use of outflow tract views, in addition to the four‐chamber view in the screening examination of the fetal heart.…”
Section: Discussionmentioning
confidence: 99%
“…There also was a high incidence of associated congenital malformations in these studies [3•]. Therefore, it can be concluded that SUA with other congenital malformations is associated with increased mortality [16].…”
Section: Incidence Of Single Umbilical Arterymentioning
confidence: 97%
“…If these patients have SUA and additional congenital defects, they more often are cardiovascular or gastrointestinal [32]. These children usually had low birth weight as infants and tend to be born prematurely [15,16]. With regards to their genitourinary anomalies, vesicoureteral reflux was identified frequently [14••].…”
Section: Incidence Of Genitourinary Malformations In Children With Simentioning
confidence: 99%